Screening and evaluation of plant seeds for coagulation property and potential as natural coagulant for water purification - Rocha, Jessamine A.; Fuentes, Rolly G. (2016)
Access to safe drinking water is still a widely occurring problem in developing countries especially in rural areas. The use of plant-based coagulants may serve as a solution to this because of the affordability, bioavailability and safeness compared to synthetic alum. This study aims to investigate the potential of seed extracts from Cassia alata, Leucaena leucocephala, and Caesalpinia pulcherrima as effective coagulants for water treatment. Among the three coagulants, C. pulcherrima showed the highest percent coagulation with 84.44% while C. alata and L. leucocephala had 71.62% and 69.34% respectively. Statistical analysis shows that the addition of the screened natural coagulants caused a significant decrease on the initial turbidity of negative control implicating that all coagulants had the ability to coagulate waters thus have potential as natural coagulants. The turbidity removal efficiency of C. pulcherimma was further tested at medium turbidity level initially having 116 Nephelometric Turbidity Unit (NTU). It was observed that the coagulant was most effective at 3 ml/500 ml volume of coagulant with 92.67% turbidity removal rate and presented no variation in pH upon addition of coagulant. This study also suggests that the seed extract of C. pulcherrima is almost as effective as the widely studied natural coagulant Moringa oleifera as per statistical data revealed.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.
Keywords: Science and technology